2013
DOI: 10.1093/jnci/djt310
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic and Genomic Investigation Into the Obesity Paradox in Renal Cell Carcinoma

Abstract: Our findings suggest that although BMI is not an independent prognostic factor for CSM after controlling for stage and grade, tumors developing in an obesogenic environment may be more indolent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
192
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 253 publications
(213 citation statements)
references
References 34 publications
17
192
3
1
Order By: Relevance
“…In the present study, morbidly obese patients with RCC treated with surgery were younger, had lower grade tumours, and were less likely to have metastatic RCC at presentation, similar to other studies [6,21]. Multivariate analysis was used to independently evaluate predictors of cancer outcomes and the present study did not identify obesity as a predictor of recurrence or cancer mortality, despite considering multiple BMI definitions of obesity and other known predictive variables.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In the present study, morbidly obese patients with RCC treated with surgery were younger, had lower grade tumours, and were less likely to have metastatic RCC at presentation, similar to other studies [6,21]. Multivariate analysis was used to independently evaluate predictors of cancer outcomes and the present study did not identify obesity as a predictor of recurrence or cancer mortality, despite considering multiple BMI definitions of obesity and other known predictive variables.…”
Section: Discussionsupporting
confidence: 76%
“…Given that the incidence of both RCC [18] and extreme obesity [9] are increasing, urologists will increasingly have to consider the potential benefits of treatment vs the higher risk of surgical and anaesthetic complications in very obese patients [19]. Recent studies have suggested that obesity increases the risk of developing RCC [1], although mild or moderate obesity is not necessarily associated with worse outcomes [4][5][6][7][19][20][21][22]. In the present study, we evaluated the largest series to date of RCC patients with extreme obesity, and found similar CSS and recurrence rates when compared with patients with lower body mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Paradoxically, higher BMI appears to be associated with better prognosis among RCC patients. 3,4 As BMI is an indirect measure of adiposity that does not distinguish between adipose tissue and lean mass, 5 other metrics of body size should be considered in relation to RCC prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furberg, Hakimi and their colleagues pulled up the medical data from these 126 people and calculated each patient's BMI just before surgery 4 . They wanted to see if a person's BMI had any bearing on the tumours' gene expression.…”
Section: Finding the Mechanismmentioning
confidence: 99%